Evolutionary dynamics of the accessory genome of Listeria monocytogenes. - Henk C den Bakker (Public Library of Science (PLoS), 2013)
Listeria monocytogenes, a foodborne bacterial pathogen, is comprised of four phylogenetic lineages that vary with regard to their serotypes and distribution among sources. In order to characterize lineage-specific genomic diversity within L. monocytogenes, we sequenced the genomes of eight strains from several lineages and serotypes, and characterized the accessory genome, which was hypothesized to contribute to phenotypic differences across lineages. The eight L. monocytogenes genomes sequenced range in size from 2.85-3.14 Mb, encode 2,822-3,187 genes, and include the first publicly available sequenced representatives of serotypes 1/2c, 3a and 4c. Mapping of the distribution of accessory genes revealed two distinct regions of the L. monocytogenes chromosome: an accessory-rich region in the first 65° adjacent to the origin of replication and a more stable region in the remaining 295°. This pattern of genome organization is distinct from that of related bacteria Staphylococcus aureus and Bacillus cereus. The accessory genome of all lineages is enriched for cell surface-related genes and phosphotransferase systems, and transcriptional regulators, highlighting the selective pressures faced by contemporary strains from their hosts, other microbes, and their environment. Phylogenetic analysis of O-antigen genes and gene clusters predicts that serotype 4 was ancestral in L. monocytogenes and serotype 1/2 associated gene clusters were putatively introduced through horizontal gene transfer in the ancestral population of L. monocytogenes lineage I and II.